2019
DOI: 10.4236/opj.2019.95007
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of the Hydrogen Atom under Different Potential Well

Abstract: In this work we studied the behavior of hydrogen atom under different potential well and found that with decreasing the distance between the electron and proton, the more multiple interaction terms start to take effect and the potential well becomes more and more sensitive to the distance between the electron and proton. Based on these results, the potential well for the neutron decaying is determined. Furthermore, the general topics, such as the origin of nuclear energy, the fundamental forces in the nature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In our previous work [14], we pointed out that our spacetime is the electromagnetic spacetime and all matters in our universe are made from the compressed spacetime, therefore, an hydrogen atom in our spacetime looks like a piece of ice floating in water. Around the hydrogen atom distributed the electromagnetic wave.…”
Section: The Effect Of the Cosmic Background Radiation (Cmb)mentioning
confidence: 97%
See 1 more Smart Citation
“…In our previous work [14], we pointed out that our spacetime is the electromagnetic spacetime and all matters in our universe are made from the compressed spacetime, therefore, an hydrogen atom in our spacetime looks like a piece of ice floating in water. Around the hydrogen atom distributed the electromagnetic wave.…”
Section: The Effect Of the Cosmic Background Radiation (Cmb)mentioning
confidence: 97%
“…As we pointed out in our previous work [14], for Einstein's explanation of the Gravity, there exist at least two shortcomings:…”
Section: The Unification Of the Gravity And The Electromagnetic Forcementioning
confidence: 98%
“…This equation tells us that for the hydrogen atom at ground state, its energy for keeping the hydrogen atom in stability can be obtained by applying the Hamilton operator onto the system and integrating over whole space. Our previous work demonstrated that the main role in keeping the hydrogen atom in stability comes from the electromagnetic energy of system [11][12][13], therefore, we can get,…”
Section: Theoretical Considerationmentioning
confidence: 97%